Probiotic potential and biotherapeutic effects of newly isolated vaginal Lactobacillus acidophilus 36YL strain on cancer cells - Nami, Yousef; Abdullah, Norhafizah; Haghshenas, Babak; Awang Biak, Dayang Radiah; Rosli, Rozita; Khosroushahi, Ahmad Yari (Elsevier, 2014)
Lactobacillus acidophilus is categorized as a probiotic strain because of its beneficial effects in human health and prevention of disease transmission. This study is aimed to characterize the probiotic potential of L. acidophilus 36YL originally isolated from the vagina of healthy and fertile Iranian women. The L. acidophilus 36YL strain was identified using 16S rDNA gene sequencing and characterized by biochemical methodologies, such as antibiotics susceptibility, antimicrobial activity, and acid and bile resistance. The bioactivity of the secretion of this strain on four human cancer cell lines (AGS, HeLa, MCF-7, and HT-29) and one normal cell line (HUVEC) was evaluated by cytotoxicity assay and apoptosis analysis. This newly isolated strain was found to exhibit notable probiotic properties, such as admirable antibiotic susceptibility, good antimicrobial activity, and favorable resistance to acid and bile salt. The results of bioactivity assessment demonstrated acceptable anticancer effects on the four tested cancer cell lines and negligible side effects on the assayed normal cell line. Our findings revealed that the anticancer effect of L. acidophilus 36YL strain secretions depends on the induction of apoptosis in cancer cells. L. acidophilus 36YL strain is considered as a nutraceutical alternative or a topical medication with a potential therapeutic index because of the absence of cytotoxicity to normal cells, but effective toxicity to cancer cell lines.